2015
DOI: 10.1001/jama.2014.16968
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Bariatric Surgery and Long-term Survival

Abstract: Among obese patients receiving care in the VA health system, those who underwent bariatric surgery compared with matched control patients who did not have surgery had lower all-cause mortality at 5 years and up to 10 years following the procedure. These results provide further evidence for the beneficial relationship between surgery and survival that has been demonstrated in younger, predominantly female populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
246
2
16

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 410 publications
(269 citation statements)
references
References 38 publications
5
246
2
16
Order By: Relevance
“…Numerous studies have demonstrated that bariatric surgery is safe and effective [3,4,22,23]. There is also strong observational data suggesting that bariatric surgery is beneficial for at least 10 to 20 years [5,24]. Increased dissemination of this evidence to PCPs and medical trainees may lead to prioritization of obesity treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that bariatric surgery is safe and effective [3,4,22,23]. There is also strong observational data suggesting that bariatric surgery is beneficial for at least 10 to 20 years [5,24]. Increased dissemination of this evidence to PCPs and medical trainees may lead to prioritization of obesity treatment.…”
Section: Discussionmentioning
confidence: 99%
“…-"So, I actually have a patient, where she is so skinny [ Other PCP concerns, such as the long-term effectiveness of bariatric surgery, cannot be addressed solely with education and improved communication. Although bariatric surgery has been shown to provide a mortality benefit as far as 10 years following surgery [5], there are notable gaps in the literature. Weight loss and co-morbidity resolution outcomes 410 years after bariatric surgery are poorly reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Bariatric surgery is associated with improved long-term survival in morbidly obese patients. 8 Not surprising, the number of bariatric procedures performed annually has increased globally to 468,609 procedures in 2013 9 with…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery has reduced morbidity and mortality from these disease and others. 2 causing a high rise in the amount of these surgical procedures performed annually. Of the possible bariatric procedures available, Roux en Y gastric bypass (RYGB) is still the most common surgical procedure.…”
Section: Introductionmentioning
confidence: 99%